The cycle of violence: links between previous victimisation patterns and internalized violence (self-harm) in young offenders - Teng, Grace Xue En (2017)
Many studies have suggested that past victimisation experience is a significant risk factor for self-harming behaviour (SHB) (Gratz, Conrad & Roemer, 2002; Gratz 2003; Glassman, Weierich, Hooley, Deliberto & Nock, 2007). This study aimed to explore the association of childhood victimisation patterns (intra and extrafamilial abuse) and types of SHB (direct and indirect SHB). Information of 166 young people who stayed within a secure unit was obtained for data analysis. Sexual abuse showed a strong significant link to types of SHB. However, this was not found for physical abuse. The observed association showed that intrafamilial sexual abuse was more positively correlated to both direct and indirect SHB compared to extrafamilial sexual abuse. Results suggested that sexual abuse was associated with the development of SHB. Also, in terms of sexual abuse, intrafamilial abuse may have more adverse consequences compared to extrafamilial abuse. Findings from this study and their implications are discussed within this paper.